The making of a lost generation: Child labor among Syrian refugees in Turkey - Meltem Dayıoğlu; Murat G. Kirdar; İsmet Koç (Koç University-TÜSIAD Economic Research Forum (ERF), 2021)
Millions of children are forcibly displaced around the world, making child labor a serious risk. However, little is known about this topic due to the difficulty of finding representative datasets for this population and information on child labor. In this study, we use a representative dataset on Syrian refugees in Turkey, the largest refugee group in any single country, to examine the incidence of child labor and its determinants. The incidence of paid work is remarkably high among boys: 17.4% of 12-14 year-olds and 45.1% of 15-17 year-olds are in paid employment. We find that paid work is positively associated with poverty, proficiency in Turkish, living in an industrialized region in Turkey, originating from rural areas in Syria and living in a household with a young, female, or less-educated head. Family composition matters more for girls' employment than boys'. Boys' (girls') employment increases if their father (mother) is alive - suggesting network effects. Being older at arrival is highly associated with child labor, indicating that difficulty with school integration drives children into employment.
Keywords: J13; J15; J61; O15; O53; 330; child labor; forced displacement; Syrian refugees; paid work; migrants; Turkey